Dating Methods of Pleistocene Deposits and Their Problems: The Promise of Atom Counting - Litherland, Albert (Geoscience Canada)

(untitled) (The Geological Association of Canada, 1979)
Summary Recent developments in mass spectrometry, using some of the apparatus and techniques of nuclear physics, have made possible the detection of the cosmic ray created ''C, U)Be and -«-'C1 nuclei at natural concentrations by atom counting. The small sample size, a few milligrams, promises to revolutionize' aC dating and to introduce new dating methods for the Pleistocene